Analisis Penggunaan Media Pembelajaran Microsoft Sway dalam Pembelajaran Menulis Teks Deskripsi Pada Siswa Kelas VII Sekolah Menengah Pertama Negeri 2 Kutawaluya - Windu Wulan; Wienike Dinar Pratiwi; Een Nurhasanah (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to analyze the use of Microsoft Sway learning media in learning to write descriptive text with the background of the lack of use of Microsoft Sway in learning and the lack of student motivation. This research is a qualitative research. The subjects in this study were seventh grade students of State Junior High School 2 Kutaluya. The method used in this research is descriptive qualitative research method. Data collection techniques in the form of student assignments and learning outcomes of writing descriptive text. The data analysis technique in this research is descriptive analysis. The results of this study are: 1) Before using Microsoft Sway learning media, there are problems with students, namely the lack of student motivation in learning to write descriptive text. This is due to the lack of effective learning media used by teachers. 2) After using Microsoft Sway learning media, students were very enthusiastic about the use of learning media used by teachers (researchers). The results of this study can be said to be effective, because it can increase students' enthusiasm for learning and learning motivation.